Are degraded karst tiankengs coupled with microclimatic underground forests the refugia of surface flora? Evidence from China’s Yunnan - Shui, Wei; Liu, Yuanmeng; Jiang, Cong; Sun, Xiang; Jian, Xiaomei; Guo, Pingping; Li, Hui; Zhu, Sufeng; Zong, Sili; Ma, Meiqi (Frontiers in Ecology and Evolution, 2022)
Karst tiankengs, as one of the most magnificent negative topographies, are capable of forming a bank for species diversity conservation easily. More than 300 karst tiankengs have been discovered and identified worldwide. Given its treacherous terrain, although original karst tiankeng were identified as species refuges, the broader distribution of degraded karst tiankeng has not been systematically studied. Our study area comprised the degraded karst tiankeng cluster immersed in the fragmented karst forests of Yunnan, China. Fifty-eight plant samples were selected from karst tiankengs and surface. We compared species composition, and analyzed diversity indices and similarity coefficients to verify the isolation effect of karst tiankengs on floras. The results indicated that: (1) There were 24 families, 37 genera and 48 species in the tree layer and 27 families, 43 genera and 49 species in the shrub layer of the karst tiankengs. Outside the karst tiankengs, 20 families, 31 genera and 39 species were in the tree layer, and the shrub layer included 26 families, 44 genera and 55 species. (2) The species composition reached significant differences within and outside the karst tiankeng (p<0.05) based on the analysis of variance (ANOVA). (3) Species richness/diversity in trees were higher than those in the shrub layer in karst tiankengs, while at the surface, shrubs had higher richness and lower diversity than trees by Alpha-diversity index. For Beta-diversity index, species similarity among karst tiankengs (0.215) was extremely dissimilar, which was even lower than the contrast within and outside the karst tiankengs (0.272). (4) Shared species ranged from 1 to 5 among the four habitats, with high variability in plant species across the habitat matrices. Through a comparative analysis of systematic biodiversity methods, we found that the degraded karst tiankengs, an independent type of karst tiankeng, are the unreported refugia. Species records in karst tiankeng cluster will contribute to the plant diversity conservation and resource management and to the linkage with the broader China’s karst floras. Karst tiankeng botanical habitats possess not only biodiversity value for in-situ conservation, but will further support the ecological recovery of surface flora. While its mechanism needs to be further revealed.